Rural extension with a focus on sustainable development objectives: a global and local analysis (Research, Society and Development, 2020)
This paper aims to make a bibliographic review about of rural extension in Brazil and in the World with a focus on goal number two of the ODS, which aims at zero hunger and sustainable agriculture. For this, was made a search for the main scientific bases aiming to select references in the study of rural extension focusing on the objectives of sustainable development. The structuring of this work was based on the understanding of the world and national context, verifying the influences of rural extension before and after 2015 (The Sustainable Development Agenda 2030), results and technology transfer and finally the discussions and considerations. The results indicate the need for the State to dedicate itself to regular public and private extension services, so that there are no discovered producers of extension services, as well as to promote with producers and family farmers sustainable practices of agricultural production, such as a way of meeting the growing demands for healthy food and maintaining a sustainable agricultural practice.